Dialectics of Rational Change Management in Regional Social Systems - Tatarkin, Aleksandr Ivanovich; Krivenko, Natalya Vasilyevna; Kuznetsova, Nataliya Lvovna (Economy of Regions, 2015)
In the article, the attention is paid to a role of service-producing industries rendering social services, promoting human development in the modern state. Theoretical positions of scientists considering meaning of the social benefits and need of active state support of the social sphere are generalized. The condition of the Russian service-producing industries is considered, the comparative analysis of indicators of their activity with indicators of service-producing industries of other countries is carried out. In view of indicators of the efficiency ratings of national education systems, world countries on the health systems efficiency, world countries on the level of social development of 2014, the author's conceptual approach is offered; it considers interconditionality and interdependence of level of public financing of the social sphere and dynamics of a contribution of service-producing industries to the human capital development providing a gain of gross domestic product of the country. Need of innovative changes in socio-economic systems of service-producing industries for the efficiency increase of their activity, taking into account the received results - first of all in health care is proved. Theoretical approaches to management of changes in socio-economic systems are investigated. On the basis of the conducted research, the created theoretical basis of the level increase of change management in open socio-economic systems for the purpose of the theoretical and methodological approaches to development to change management in relation to health sector, the optimization model of management of health care organizations ranging controlled and uncontrollable changes is offered. The use possibilities of management optimization by ranging controlled and uncontrollable changes in health sector of different management levels are confirmed by the high rates of performance efficiency on micro-, meso- and macrolevel in industry on the example of implementation of national project Health and innovative organizational transformations promoting the return to work of the patients of working-age participating in development of gross domestic product across Yekaterinburg.